To be or not to be Yuval Noah Harari's Homo Deus - Krzanowski, Roman (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
Book review: Homo Deus. A Brief History of Tomorrow. Yuval Noah Harari. Vintage, UK. 2017. p. 512.
Keywords: anthropology; philosophy